Peran Organisasi Santri Gabungan Anak Timur Sekitar Dalam Mengembangkan Ghirah Pembelajaran di Musthafawiyah Purba Baru - Cipto Halomoan Ritonga; Wedra Aprison (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
The purpose of this research is 1) to look at the history of the founding of the East Surrounding Children's Association organization in Mustafawiyah. 2) To see the role of the Surrounding Eastern Children's Association organization in maintaining the passion for learning in Musthafawiyah Purba Baru. This type of research is a qualitative research type with a qualitative descriptive approach method. Data collection techniques in this research are observation, interviews and documentation. Data analysis techniques use data reduction and data presentation. The data source in this research is the management of the Association of Surrounding Eastern Children (GATIS). The results of this research are 1) that in the East Surrounding Children's Association organization which was founded on September 28 2015, which was spearheaded by alumni and continued by the seventh class, among those who participated in establishing this organization were: Ilhan Syahfutra, Maulana Malik Ibrahim and Muhammad Yusuf. 2) The role of the surrounding Eastern Children's Association organization in developing Ghirah, they create several activities which can increase their enthusiasm for learning, including: Carrying out Mudzakarah, Special Guidance, holding competitions between fellow branch organizations, etc.